2010
DOI: 10.1373/clinchem.2009.134122
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiochemical Markers of Brain Damage in Cerebrospinal Fluid of Acute Ischemic Stroke Patients

Abstract: Background: Ischemic injury to the central nervous system causes cellular activation and disintegration, leading to release of cell-type–specific proteins into the cerebrospinal fluid (CSF). We investigated CSF concentrations of myelin basic protein (MBP), glial fibrillary astrocytic protein (GFAP), the calcium-binding protein S100B, and neuron-specific enolase (NSE) in acute ischemic stroke patients and their relation to initial stroke severity, stroke location, and long-term stroke outcome. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 35 publications
4
71
0
5
Order By: Relevance
“…Therefore, it is likely that this increase represents MBP fragments generated from tissue injury and/or synthesis of de novo protein that is subsequently degraded due to lack of cellular support. This result is consistent with the fact that MBP has been suggested as a biomarker for stroke in the clinic due to documented increases in injured tissues (21).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is likely that this increase represents MBP fragments generated from tissue injury and/or synthesis of de novo protein that is subsequently degraded due to lack of cellular support. This result is consistent with the fact that MBP has been suggested as a biomarker for stroke in the clinic due to documented increases in injured tissues (21).…”
Section: Discussionsupporting
confidence: 90%
“…6B). An antibody generated against MBP was used to evaluate striatal white matter damage in rats subjected to MCAO (21). Following MCAO, increased MBP immunoreactivity was detected throughout the infarct (Fig.…”
Section: Delayed Hucb Cell Treatment Increased Akt Phosphorylation Inmentioning
confidence: 99%
“…A large number of activated S100B protein which is produced by glial cells is released into the extracellular after brain tissue injury [17], and then leaks into CSF and blood through damaged blood brain barrier, and S100B level in serum is positively correlated with the severity of the injury of cerebral ischemia [18]. Brouns and his group have also found that the concentration of S100B, which is in the cerebral spinal fluid (CSF) of the patients with acute ischemic stroke, is highly correlated to the severity of the injury and the prognosis of cerebral ischemia [19]. Under normal circumstances, NSE content is not high in blood, however, along with the necrosis of neurons and the disintegration of nerve myelin, NSE is released into CSF from the cells after cerebral ischemia injury, and then leaks into blood through the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This would explain why survival is maximal in MT-and GFAP-rich media [2,[7][8][9][10][11] and possibly why this induced attack causes the respective changes noted in these proteins. GFAP release mirrors injury to astrocytes located both in the white and gray matter and may increase owing to damage to glial cells [35]. Endogenous MT is thought to be actively secreted by astroglia and picked up by neurons through the low density lipoprotein receptorrelated protein 2 (LRP-2/megalin) and the LRP-1 receptor [36].…”
Section: Fig 2 the Level Of Metallothionein In The Rat Brain Here mentioning
confidence: 99%